Efficacy and safety of a generic remifentanil formulation versus fentanyl and Ultiva during general anaesthesia: A phase III, prospective, multi-centric, observer-blind, randomised controlled trial - Indrani Hemantkumar; Ashok Kumar Swain; Manjaree Mishra; Swati Singh; Challakere Lakshminarain Gurudatt; Janampet Bekkam Giridhar (Indian Journal of Anaesthesia)
Background and Aims: Remifentanil and fentanyl are potent opioid analgesics commonly used during surgery due to their distinct pharmacological profiles. This study aimed to compare the efficacy and safety of a generic remifentanil (test drug) with fentanyl and Ultiva (innovator formulation) during general anaesthesia in the Indian population. Methods: This phase III, multi-centre (n = 13), randomised, three-arm, comparative study was conducted from 24 November 2021 to 31 March 2022. Eligible subjects scheduled for elective therapeutic and diagnostic surgical procedures (n = 314) were randomised into generic remifentanil, Ultiva, and fentanyl groups. An independent anaesthetist blinded to treatment allocation assessed efficacy and safety parameters. The primary efficacy endpoint was haemodynamic response during specific activities (endotracheal intubation, skin incision, skin closure, and extubation). Results: The study groups exhibited no significant differences in demographic and baseline characteristics. Heart rate was similar between the remifentanil and Ultiva groups measured during laryngeal intubation, skin incision, skin closure, and extubation (P > 0.05 in all four procedures). Heart rate was significantly higher in the fentanyl group in comparison to the remifentanil group during laryngeal intubation (P = 0.035), skin incision (P = 0.017), skin closure (P = 0.001), and extubation (P = 0.026). The need for vasopressor and anti-cholinergic drugs was similar between groups, and no subject required naloxone administration. Conclusion: Our study’s findings demonstrated that generic remifentanil is non-inferior to fentanyl and equivalent to Ultiva for general anaesthesia in Indian patients undergoing various surgical and diagnostic procedures. Remifentanil offers advantages in terms of optimum haemodynamic stability, fast equilibrating analgesia, and rapid emergence from sedation, making it a suitable alternative to fentanyl.